Pengembangan Strategi Marketing UMKM dan Atraksi Wisata Desa Wisata Tepus Gunungkidul - Ayu Helena Cornellia (Jurnal Abdimas Pariwisata, 2023)
Development of UMKM Marketing Strategy and Tourist Attractions in Tepus Gunungkidul Tourism Village Community Service Activities are tasks or obligations that must be carried out as a routine activity of an organization or company. In 2022, the Ampta Tourism High School community service will be carried out in one of the Tourism Villages in Gunungkidul Regency, namely the Tepus Tourism Village. STP Ampta surveyed the Tepus Tourism Village, FGDs with Tepus Tourism Village HR, analyzed the problems that the Tepus Tourism Village had, found the right solution, and conducted an evaluation and monitoring. The survey results found that the Tepus Tourism Village human resources were not literate and aware of digital marketing. So that this service activity focuses on digital marketing support for the village, all human resources in the Tepus Tourism Village are given training and guidance in processing digital marketing to promote tourist villages and MSMEs in them. With the digital marketing training provided, Tepus Tourism Village HR will realize how important it is to promote through social media. In the end, this activity can have an impact on other sectors, such as the economic sector and the cultural sector.